Calculation of the metal reflectivity with taking polarization into consideration - Vakulenko, O.V.; Severin, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Optical properties of free electrons in the conduction band of metal are
considered. It is shown that the conventional Drude theory does not take shielding of the
external electrical field by mobile electrons into account. This shielding is conditioned by
the polarization of these electrons. Offered is the way of taking this polarization into
consideration when calculating the reflectivity of metal. It is shown that the account of
polarization results in agreement between the theoretical results and experimental data.